ANALISIS YURIDIS PRINSIP HUKUM PERLAKUAN SAMA KEPADA INVESTOR DOMESTIK DAN INVESTOR ASING YANG MELAKUKAN KEGIATAN PENANAMAN MODAL DI INDONESIA - CINDY CINDY; BUDIMAN GINTING; MAHMUL SIREGAR (TRANSPARENCY, 2013)
Principle of equal treatment is where the government gives equal treatment to domestic investors and foreign investors whom undertake investment activities in Indonesia. It began when Indonesia ratifies Agreement on TRIMs (Agreement on TradeRelated Investment Measured) through the enactment of Law No. 7 of 1994 on Ratification of Agreement Establishing The World Trade Organization (the Agreement Establishing the World Trade Organization. Therefore, the problem of this thesis is how the treatment of investors under the Act and the Foreign Investment Law of Domestic Investment, why the need for equal treatment of investors in investment activities in Indonesia and how the application of the principle of equal treatment to investors in investment activities in Indonesia based on Law Number 25 Year 2007 on Capital Investment and its implementing regulations. The method used for this thesis is a normative legal research or library research, by collecting materials from books, legislation, journals and the Internet are closely related to the intent and purposes of the preparation of this manuscript. The treatment of investors under the Law of Foreign Investment and Domestic Investment have differences both in the fields of business, labor and other fields. The need for the legal principle of equal treatment for developed countries to invest in developing countries, with the investment, the development of local communities because of the attention and influence of international agreements. Principle of equal treatment set forth in Law No. 25 of 2007 regarding Capital Investment Article 4 paragraph (2) and Article 6. Keywords: Perlakuan Sama, Investor